2022
DOI: 10.3389/fphar.2022.841766
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 Receptors Modulate Microglia Function and Amyloid Dynamics in a Mouse Model of Alzheimer’s Disease

Abstract: The distribution and roles of the cannabinoid CB2 receptor in the CNS are still a matter of debate. Recent data suggest that, in addition to its presence in microglial cells, the CB2 receptor may be also expressed at low levels, yet biologically relevant, in other cell types such as neurons. It is accepted that the expression of CB2 receptors in the CNS is low under physiological conditions and is significantly elevated in chronic neuroinflammatory states associated with neurodegenerative diseases such as Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…We detected in the electron microscope the presence of plaques and a multitude of dystrophic neurites in the 5xFAD/CB 2 EGFP/f/f mice that confirms the usefulness of this animal model for studying the pathophysiology of AD (Ruiz de Martín Esteban et al, 2022). We also observed an overt microglial and astrocytic reactivity with an increase in the area and perimeter of their processes, demonstrating the existence of significant alterations in the subicular cytoarchitecture.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We detected in the electron microscope the presence of plaques and a multitude of dystrophic neurites in the 5xFAD/CB 2 EGFP/f/f mice that confirms the usefulness of this animal model for studying the pathophysiology of AD (Ruiz de Martín Esteban et al, 2022). We also observed an overt microglial and astrocytic reactivity with an increase in the area and perimeter of their processes, demonstrating the existence of significant alterations in the subicular cytoarchitecture.…”
Section: Discussionsupporting
confidence: 77%
“…We hypothesize in this study that CB 1 receptor expression in glia is altered in the subiculum of a mouse model of AD, a brain region particularly affected by large accumulation of plaques, as a result of concomitant subcellular changes in microglia and astrocytes. Our findings show that CB 1 receptors in microglial cells suffer remarkable modifications in 5xFAD/CB 2 EGFP/f/f mice, a murine model of AD recently reported to have an increase in CB 2 receptors in microglia related to dystrophic neurites (Ruiz de Martín Esteban et al, 2022), similarly to the CB 2 rise observed in plaque‐associated microglia (Benito et al, 2003, 2007).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Further investigations by electron microscopy revealed the presence of low EGFP signal in the membrane of some Iba1-positive cells in the subiculum of CB2 EGFP/f/f mice, and at higher levels in both membrane and cytosol of Iba1-positive cells from CB2 EGFP/f/f /5xFAD mice. 86 In retina, EGFP signal was sparse at baseline in microglial elements, but upregulated following inflammatory stimuli. 87 Efforts must be made to support the development of bettervalidated antibodies in each species in which the CB2R protein is assessed or must be quantified.…”
Section: Con Cluding Remark Smentioning
confidence: 99%
“…Indeed, CB2R EGFP/f/f transgenic mice display no expression of CB2Rs in the healthy CNS, while they show an upregulation in reactive microglia in response to inflammation in mice expressing five familial Alzheimer's disease mutations CB2R EGFP/f/f /5XFAD (López et al, 2018). Using electron microscopy in CB2R EGFP/f/f mice, the same group observed a low expression in microglial cells compared to CB2R EGFP/f/f /5xFAD mice (Ruiz de Martín Esteban et al, 2022).…”
Section: Microglial Cb2r Signaling In Physiological Conditionsmentioning
confidence: 95%